1985
DOI: 10.2140/pjm.1985.119.125
|View full text |Cite
|
Sign up to set email alerts
|

G-bordism with singularities andG-homology

Abstract: The bordism and cobordism theories of singular G-manifolds of specified kinds are used to represent various ordinary G-homology and cohomology theories, and their relationship to each other, as well as their relationship to non-singular G-bordism, is studied.1. Introduction. Sullivan once pointed out that ordinary homology may be viewed geometrically as a bordism theory with singularities. This has been formally established by Baas in [1] and by Buoncristiano, Rourke and Sanderson in [3]. Dually, the associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Basics. In [8], Hastings and Waner showed that ordinary RO(G)-graded equivariant homology could be defined using bordism of manifolds with a certain kind of singularity, similar to the Baas-Sullivan approach nonequivariantly. The Hastings-Waner result can be generalized to show that ordinary RO(ΠB)-graded homology can be given by bordism of singular manifolds as well.…”
Section: Singular Manifoldsmentioning
confidence: 99%
“…Basics. In [8], Hastings and Waner showed that ordinary RO(G)-graded equivariant homology could be defined using bordism of manifolds with a certain kind of singularity, similar to the Baas-Sullivan approach nonequivariantly. The Hastings-Waner result can be generalized to show that ordinary RO(ΠB)-graded homology can be given by bordism of singular manifolds as well.…”
Section: Singular Manifoldsmentioning
confidence: 99%